2007
DOI: 10.1111/j.1532-849x.2007.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Denture Base Resins Potentially Resistant to Candida Adhesion

Abstract: Within the limitations of this study, the physical properties of the phosphate denture base resin at 10% should be suitable for denture fabrication based on the properties assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
92
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 30 publications
2
92
0
12
Order By: Relevance
“…As part of our continuing studies, these phosphated polymers were examined for their physical and mechanical properties and the data were published previously. 21,22 These studies have shown that the incorporation of phosphate into an acrylic resin denture material by monomer substitution did not affect its impact strength, fracture toughness, and resin bonding ability to artificial teeth. 22 They also suggest that physical properties such as water sorption and solubility of the phosphate incorporated polymers could remain acceptable up to the addition of 10%-20% phosphate anions.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…As part of our continuing studies, these phosphated polymers were examined for their physical and mechanical properties and the data were published previously. 21,22 These studies have shown that the incorporation of phosphate into an acrylic resin denture material by monomer substitution did not affect its impact strength, fracture toughness, and resin bonding ability to artificial teeth. 22 They also suggest that physical properties such as water sorption and solubility of the phosphate incorporated polymers could remain acceptable up to the addition of 10%-20% phosphate anions.…”
mentioning
confidence: 98%
“…22 They also suggest that physical properties such as water sorption and solubility of the phosphate incorporated polymers could remain acceptable up to the addition of 10%-20% phosphate anions. 21,22 More comprehensive microbiological, mechanical, and cytotoxicity assessments and the thermal stability of the polymers are in progress to determine the potential in vivo activity and to explore the clinical utility of these materials.…”
mentioning
confidence: 99%
“…26 Akrilik rezinlerde su emilim özelliği PMMA moleküllerinin polaritesi ve su moleküllerinin polimer zincirlerinin arasındaki boşluk alanlarına difüzyonundan etkilenmektedir. 27 Ürethan dimetakrilat monomerleri moleküler yapılarında 2 hidrofilik ürethan grubu bulundururlar. Isı stresi, polimer zincirleri arasındaki mesafeyi arttırarak polimerin su emme özelliğini arttırır.…”
unclassified
“…Denture base polymers are susceptible to color change if the cleaning solutions are not correctly used 17 . The surface roughness is of great clinical relevance since it can affect biofilm formation and make it difficult to remove 18 . Therefore, the choice of appropriate methods for denture cleaning is clinically important, when the objective of the procedures is not to cause surface damage of the denture base, and for daily use to prevent microbial adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the concern for esthetics, the lack of adequate denture hygiene can cause biofilm accumulation and oral infections such as denture stomatitis 2,3 . It is a common infection characterized by inflammation of oral tissues and colonization of the fitting surface of prostheses by micro-organisms 4 .…”
Section: Introductionmentioning
confidence: 99%